(untitled) (The International Journal for Scientific Research, 2024)
The importance of this research lies in stating and defining the digital economy and digital transformation and how it is used by governments and companies to serve the national economy in Jordan. Through this importance, the main objective of this research is to state the role of the digital economy in economic development by studying several main axes, including studying the digital economy, whether in general or at the level of the Jordanian experience, and studying economic development in brief and stating some of its indicators. The indicators of gross domestic product, unemployment and inflation were chosen, and the periods before the digital transformation from 2015 - 2019 and after the digital transformation from 2020 - 2023 were studied. Through the importance of the research and its objectives, it was necessary to formulate hypotheses in order to prove or deny them, and these hypotheses were as follows: The first hypothesis: There is a positive correlation that leads to an increase in the rates of economic development in Jordan as a result of the application of the digital economy (digitization). The second hypothesis: There is a partnership between the official bodies responsible for the digital economy and other bodies, whether governmental or informal (private sector) that contribute to economic development. In order to prove or disprove these hypotheses, it was necessary to use a specific method. The descriptive analytical (quantitative) method was used by collecting data and figures for economic development indicators, with a brief statement and explanation of the digital economy in Jordan and economic development during the mentioned period before and after the digital transformation. This research was divided into five sections. In the first section, we talked about the theoretical framework of the research, the most important of which was the research plan. In the second section, we talked about the digital economy in general. In the third section, we talked about the digital economy in Jordan. As for the fourth section, we talked about economic development, and the most important section was the fifth section. We talked about testing hypotheses, results, and recommendations. Through this section and using the descriptive analytical (quantitative) method, we reached the proof of the first hypothesis mentioned, through which we proved that the digital economy has a major role and impact on economic development. As for the second hypothesis, we proved that there is actually a partnership between the parties responsible for the digital economy and other parties such as the private sector or other government sectors. Based on that, a number of results and recommendations were extracted, the most important of which are the following: Results: - The digital transformation (digital economy) has a major role in economic development, as it increases job opportunities, reduces unemployment rates, and also reduces inflation rates. It also contributes to increasing the gross domestic product. - Increasing the number of trainees on the use of modern technologies and information technology, which reduces digital illiteracy among all age groups. - The digital economy has worked to save time and effort significantly as a result of the use of modern technologies - The existence of a real partnership and effective contribution between the public and private sectors in the field of information technology and digital transformation. Recommendations: - Complete transformation and inclusion of all government services to become fully digital. - Increasing the number of trainees and encouraging learning in the use of advanced technology and establishing specialized training centers and introducing a complete curriculum for the digital economy in schools to become a digital society - Establishing a new specialization in the digital economy and approving it by the Ministry of Higher Education and Scientific Research - Increasing the budget of the Ministry of Digital Economy and urging it to innovate and conduct research for further progress and prosperity in the field of information technology so that the Kingdom becomes a competitor to the countries of the world in this field. - Removing any obstacles and impediments facing the private sector to expand its business through complete digital transformation.